Kompetensi Manajerial Penggerak Usaha Pasar Tradisional Payungi Kota Metro dalam Pemanfaatan Media Sosial untuk Keberlangsungan dan Keberlanjutan Pasar - Syafani, Tyas Sekartiara; Yanfika, Helvi; Abidatussholihat, Abidatussholihat (Fakultas Pertanian, Universitas Lampung, 2026)
Pasar Yosomulyo Pelangi (PAYUNGI) in Metro City is a creative village resulting from a community empowerment program that has successfully helped create economic independence and involved the community in building the village into a creative village. This allows the community to have their own businesses and be empowered through the available activities. As a community empowerment initiative, competence plays an important role in the sustainability and continuity of a community business group. This research was designed with the aim of understanding the managerial competence of the Payungi’s businessperson (traders) in utilizing social media to increase sales and ensure market sustainability in the Yosomulyo Pelangi market community group, as well as analyzing the relationship between social media usage and market sustainability. The research was conducted from April to September 2024, with the research area determined purposively. The respondents of this research were 50 Payungi business actors and 5 informants who are the leaders/managers of the business units. The results show that the majority of the business drivers at Payungi have medium-level competence because they are able to operate communication tools (smartphones) for business purposes through social media platforms like WhatsApp and Instagram. However, in terms of management aspects, the implementation of management functions has not reached the controlling/evaluation stage. The use of social media by Payungi members does not have a direct relationship with market sustainability, as the market's sustainability is created through the collective culture of cooperation (gotong royong) among members and the Payungi driving team as part of the Yosomulyo village community. Keywords: competence, managerial, community empowerment, social media